2023
DOI: 10.12701/jyms.2022.00010
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of intermittent fasting: a narrative review

Abstract: Caloric restriction is a popular approach to treat obesity and its associated chronic illnesses but is difficult to maintain for a long time. Intermittent fasting is an alternative and easily applicable dietary intervention for caloric restriction. Moreover, intermittent fasting has beneficial effects equivalent to those of caloric restriction in terms of body weight control, improvements in glucose homeostasis and lipid profiles, and anti-inflammatory effects. In this review, the beneficial effects of intermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…The clinical trial by Stekovic et.al in which IF was applied to a medium‐sized human cohort for a long period of time has shown that IF is more tolerable than sustained calorie restriction to improve cardiovascular system and body composition 10 . More importantly, IF has been demonstrated to be safe to practice in healthy non‐obese adults for more than 6 months 11 . Metabolic transformation of fed‐fast cycle induced by IF significantly enhances the anti‐stress and protective capacity of cells, which promotes cell repair, induces autophagy, and optimizes stress responses 12–14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical trial by Stekovic et.al in which IF was applied to a medium‐sized human cohort for a long period of time has shown that IF is more tolerable than sustained calorie restriction to improve cardiovascular system and body composition 10 . More importantly, IF has been demonstrated to be safe to practice in healthy non‐obese adults for more than 6 months 11 . Metabolic transformation of fed‐fast cycle induced by IF significantly enhances the anti‐stress and protective capacity of cells, which promotes cell repair, induces autophagy, and optimizes stress responses 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…10 More importantly, IF has been demonstrated to be safe to practice in healthy non-obese adults for more than 6 months. 11 Metabolic transformation of fed-fast cycle induced by IF significantly enhances the anti-stress and protective capacity of cells, which promotes cell repair, induces autophagy, and optimizes stress responses. [12][13][14] The impact of long-term IF before pregnancy on offspring metabolism remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Durante los períodos de ayuno, se evita la ingesta de alimentos durante un tiempo específico, que puede variar desde unas pocas horas hasta un día completo o más, seguido de períodos en los que se permite la alimentación dentro de una ventana de tiempo determinada (Song & Kim, 2023).…”
Section: Resultsunclassified
“…CR and intermittent fasting stimulates autophagy mainly by decreasing mTOR signaling by reducing insulin and IGF-1 levels and increasing the AMP/ATP ratio that leads to the activation of AMPK as well as several products involved in the stimulation of this process like ATG6, ATG7, ATG8, LC3-II, Beclin1, p62, Sirt1, LAMP2, ULK1 and ATG101 196 , 214 . The favorable effects on autophagy of both CR and intermittent fasting seems to be involved in the increase of fat mobilization, oxidation, metabolic flexibility, insulin sensitivity and redox imbalance together with a reduction in systemic inflammation, cardiovascular risks and body weight 215 . Hence, either CR or intermittent fasting are valuable and similar strategies to preserve health and aid in the clinical management of several diseases 216 .…”
Section: Modulation Of Autophagymentioning
confidence: 99%